Surface modification of Ti64-Alloy with silver silicon nitride thin films - Mohamad Zaidi, Umi Zalilah; Mahmoodian, Reza; Bushroa, Abd Razak; Vellasamy, Kumutha Malar (Taylor & Francis, 2019)
Ti6Al4V (Ti64) alloys is an alpha-beta titanium alloy with good corrosion resistance, high strength-to-weight ratio, excellent physiochemical stability and good biocompatibility. However, Ti64 alloy loses its biocompatibility when it is introduced into human tissues due to possible toxic of Vanadium (V) and Aluminum (Al) ion release. Thus, modification using silver silicon nitride films onto Ti64 via magnetron sputtering technique was proposed. In this study, a set of experimental depositing AgSiN films on Ti64 alloys using different bias voltage (0, −75, −150 and −200 V) were fabricated. The surface characterization and mechanical performance of the thin films with respect to bias voltage were studied using scanning electron microscope (SEM), atomic force microscope (AFM), X-ray diffraction (XRD), nanoindentation and scratch test. Meanwhile, the biological function of the films was tested through wettability and antibacterial tests. According to the results, all thin films showed similar morphology with the highest adhesion strength (596 mN) was obtained for AgSiN thin film deposited at −75 V. The hardness (5.5 GPa) and elastic modulus (211.0 GPa) of sample deposited at −150 V showed an improvement for about 50% compared to the Ti64 substrate (H = 2.75, E = 113.8). The lowest compressive residual stress 0.06 GPa was noted for samples that have highest adhesion strength and highest thickness. In terms of biological functionality, all films showed hydrophilic property with wetting angle observed were below 90°. An inhibition zone area that observed on Bulkholderia pseudomallei (B.Psudomallei) and Escherichia coli (E.coli) were 7 and 10 mm respectively, which proved the AgSiN films as a promising candidate to be used in antibacterial applications.